Transformasi Gerwani: Keterlibatan dalam Perjuangan Gender Hingga Stigmatisasi Pasca 1965 - Rania Dhiyaulhaq Aisyah (Jurnal Sejarah Indonesia, 2025)
This article examines the transformation of Gerwani (Indonesian Women's Movement) as a women's organization actively involved in gender struggles in Indonesia, as well as the impact of stigmatization that emerged after the events of 1965. Using qualitative methods and a literature study approach, this research examines historical sources, academic articles, and related documents to understand the changing role and image of Gerwani over time. The findings indicate that Gerwani initially played a significant role in the fight for women's rights, education, and gender equality. However, after the events of 1965, the organization underwent a drastic image shift, with its members stigmatized as part of a political movement associated with the G30S (G30S) incident. This stigmatization resulted in the silencing of gender struggles and the marginalization of its members in Indonesian socio-political history. This article seeks to explore the complexity of Gerwani's narrative in Indonesian history and its implications for the women's movement today.